2023
DOI: 10.1093/nutrit/nuad044
|View full text |Cite
|
Sign up to set email alerts
|

Body image and dietary habits in adolescents: a systematic review

Abstract: Context Adolescence is a critical developmental stage in which increasing concerns about body image (BI) coincide with the consolidation of dietary habits (DHs). Multiple studies have sought robust associations between BI and DHs to prevent unhealthy behaviors. Objective The aim of this systematic review was to examine the available literature on the association between BI perception (BIP) and/or satisfaction (BIS) and DHs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
6
0
1
Order By: Relevance
“…In this research, female participants showed greater dissatisfaction with their bodies than males, although the percentages recorded in the two tools used (EDI 3-RF and BSQ) were different. Studies show that this dissatisfaction is more common among adolescent girls because, among other factors, at the onset of puberty there is an increase in weight resulting in a higher proportion of body fat [ 39 , 40 , 41 ]. It could also be attributed to the fact that pubertal changes tend to be later in boys [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, female participants showed greater dissatisfaction with their bodies than males, although the percentages recorded in the two tools used (EDI 3-RF and BSQ) were different. Studies show that this dissatisfaction is more common among adolescent girls because, among other factors, at the onset of puberty there is an increase in weight resulting in a higher proportion of body fat [ 39 , 40 , 41 ]. It could also be attributed to the fact that pubertal changes tend to be later in boys [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This divergence could be due to the social influence with ideal body types, as girls lean towards slimmer body shapes and therefore engage in what they perceive as weight-reducing behaviors, while boys prefer to have a muscular body and wish to gain weight. In addition, teenage boys tend to underestimate their weight while girls tend to overestimate their weight [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In its conformation, it includes evaluative aspects (such as satisfaction or concern with appearance) mainly regarding shape and weight and is strongly influenced by social, ethnic, cultural and economic conditions [7]. BI is linked to personal confidence, self-esteem, eating and exercise behaviors and other factors that can interfere with people's daily lives and well-being [8].…”
Section: Adequate Adolescent Develop-mentmentioning
confidence: 99%
“…Body image (BI) is a psychological term related to self-image that predominantly refers to the visual representation of one’s own body shape and size, regardless of their actual body shape and size, and also includes subjective perceptions, feelings, and thoughts about that representation [ 1 ]. BI is thus a multidimensional construct that refers to one’s perceptions of and attitudes toward one’s own physical characteristics.…”
Section: Introductionmentioning
confidence: 99%